Análisis de la pobreza: aspectos teóricos y su aplicación al caso argentino (1980-2000) - María Emma Santos (Estudios Económicos, 2002)
Análisis de la pobreza: aspectos teóricos y su aplicación al caso argentino (1980-2000)